(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
Flofee Bloom Paradise is a flower shop business conceptualized by young entrepreneurs who share the passion for flowers. They recognize its importance and use in all occasions involving their loved ones like wedding, birthday, Valentine’s Day, Teacher’s Day, graduation day and a lot more. Flowers for them can turn simple occasions to something special especially if these flowers were given by a loved one. This is the ultimate reason why the concept of flower shop was pushed and made the topic for their feasibility study. For them, delivering fresh flowers is like bringing love and happiness to whoever receives them. The researchers conducted a survey using a structured questionnaire composed of the respondent’s demographic information and 10 closed ended questions. The said survey was administered near the proposed location with 45 male respondents and 55 female respondents for a total of 100. Random sampling was applied. The researchers also conducted informal interview on them. Based on the results of the survey, 78% of the respondents agreed on the proposed business. Since the proposed location is along the highway, the respondents also expressed their approval. The strong confirmation of the respondents on the concept and location showed that establishing the Flofee Bloom Paradise will be profitable in the florist industry. Since the results of the study showed affirmation to the concept of Flofee Bloom Paradise, the researchers therefore conclude that the business is viable. However, during the course of the study, it was identified that competition is stiff for this kind of business. Therefore, the researchers recommend strong and strategic marketing plans in order to penetrate the market and ensure its sustainability.